2020
DOI: 10.1039/d0cp02387f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crystallite size on the phase transition behavior of heterosite FePO4

Abstract: The structural properties of heterosite FePO4 were found to exhibit crystallite size dependence below 50 nm; the change in the structural behavior with crystallite size is correlated with the change in the chemical bonding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…The detailed synthesis procedure for preparing different crystallite sized h-FP samples has already been reported elsewhere. 26 The synthesis procedure follows a two-step process; initially, LFP samples of different crystallite sizes were synthesized and then the h-FP samples were obtained by the chemical delithiation of the corresponding LFP samples by reacting it with potassium persulfate (K 2 S 2 O 8 ) in an aqueous solution (deionized water). The high-resolution synchrotron X-ray diffraction (XRD) studies were carried out at Beam Line 12 of INDUS-2 at RRCAT, Indore, India.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed synthesis procedure for preparing different crystallite sized h-FP samples has already been reported elsewhere. 26 The synthesis procedure follows a two-step process; initially, LFP samples of different crystallite sizes were synthesized and then the h-FP samples were obtained by the chemical delithiation of the corresponding LFP samples by reacting it with potassium persulfate (K 2 S 2 O 8 ) in an aqueous solution (deionized water). The high-resolution synchrotron X-ray diffraction (XRD) studies were carried out at Beam Line 12 of INDUS-2 at RRCAT, Indore, India.…”
Section: Methodsmentioning
confidence: 99%
“…We observe the appearance of a tetrahedrally-coordinated h-FP phase at lower crystallite sizes due to the enhanced surface energy kinetics, as substantiated by the earlier investigations. 26 The systematic experimental investigations on the h-FP structure revealed the lattice expansion at the nanoscale level, 26 and this volume expansion of nanosized h-FP with respect to bulk counterpart is a direct consequence of reduced hybridization between the Fe 3d and O 2p states, as revealed by the XAS measurements. The observed structural modifications with CS indicate a change in the bonding characteristics, which can have direct implications on the electronic properties of h-FP at the nanoscale level.…”
Section: Introductionmentioning
confidence: 99%
“…6 For olivine-type LiMPO 4 (M = Fe, Mn, Ni, Co) cathodes, the charge and discharge cycling induces a first-order phase transition between lithiated triphylite and delithiated heterosite phases. 1,2,7–9 The phase transition behavior of two-phase reactions in a spinel-type LiMn 2 O 4 cathode was also observed by in situ transmission electron microscopy (TEM), 10 which should be the reason for capacity fading compared with the LiCoO 2 cathode. 11…”
Section: Introductionmentioning
confidence: 90%
“…6 For olivine-type LiMPO 4 (M = Fe, Mn, Ni, Co) cathodes, the charge and discharge cycling induces a first-order phase transition between lithiated triphylite and delithiated heterosite phases. 1,2,[7][8][9] The phase transition behavior of two-phase reactions in a spinel-type LiMn 2 O 4 cathode was also observed by in situ transmission electron microscopy (TEM), 10 which should be the reason for capacity fading compared with the LiCoO 2 cathode. 11 The large specific surface area, high conductivity, high electrochemical activity and fast ion transportation pathway of two-dimensional (2D) materials make them ideal candidates for electrode materials of LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that the Fe 3+ amount increases with a decrease in CS due to the thermodynamics of surfaces for nanoparticles of LFP. 60 It has been suggested that the surface effects were a possible reason for the kinetic stability of the nano-sized LFP and its solid solution phase. Additionally, Fe 3+ acts as polaronic centres in LFP and enhances the electronic conductivity in addition to the reduced hopping length.…”
Section: Mo ¨Ssbauer Spectroscopy Studiesmentioning
confidence: 99%